(untitled) - Nolan, Han (San Diego, 1997)
A young girl from a dysfunctional family creates for herself an alternative world which nearly results in her death but which ultimately leads her to reality.
Keywords: Vấn đề gia đình,Family problems; Tiểu thuyết,Fiction